Different order cyclicity of the Paleozoic reef formation - V. G. Kuznetsov; L. M. Zhuravleva (Известия высших учебных заведений: Геология и разведка, 2019)
There are five great cycles of reef formation in Paleozoic — Early Cambrian, Middle—Late Ordovician, Silu-rian—Devonian, Late Visean—Serpukhovian and Permian. Their upper limits are determined by the corresponding periods of biotic crises and mass extinction events which have been at the borders of the Middle—Late Cambrian, Or-dovician—Silurian, Frasnian—Famenian, Serpukhovian—Baskirian, Permian—Triassic. Cycles differ in the reef prevalence within the planet, in the composition and group diversity of reef-building biota and the duration of reef formation. The longest Silurian—Devonian and Permian cycles are divided with periods of relative decrease in the intensity of reef building into two parts and these periods are clearly observed. These are second order cycles. The bases of this division are global paleogeographic and paleoclimatic causes, and at the beginning of Devon, perhaps, in addition to these reasons, an important role was played by the global biotic event — the appearance of terrestrial biota and, accordingly, a certain redistribution of the flow of nutrients from the ocean to land. In all cases, third-order cycles have been established, the formation of which is determined by purely regional-geological reasons, such as sea level fluctuations, salinity of basins, which are fixed by the overlap of reefs with terrigenous, clay or saline rocks. Similar role is played by the volcanism, as explosive activity stops the growth of reefs.